2023
DOI: 10.1002/ase.2258
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, emotions, and thoughts of veterinary medicine students during their first visit to the dissection room

Abstract: The use of cadavers is essential for veterinary anatomy learning. However, facing an animal corpse can be stressful for veterinary students because of their empathy toward animals. The objective of this study was to evaluate veterinary medicine students' emotions, feelings, and anxiety levels related to practicals with dog cadavers. Two questionnaires were administered to 1st year students (n = 168) at CEU Cardenal Herrera University in Valencia (Spain) before and after their first practical session with cadav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Peer and tutor‐student discussions have been described as methods to reduce stress on medical students prior to medical dissection courses 51 . Our results suggest that videos may also improve both the learning and emotional aspects of a slaughterhouse visit, which is supported by a recent study in which videos effectively reduced anxiety scores and improved emotional preparedness of veterinary students prior to anatomy teaching 43 …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Peer and tutor‐student discussions have been described as methods to reduce stress on medical students prior to medical dissection courses 51 . Our results suggest that videos may also improve both the learning and emotional aspects of a slaughterhouse visit, which is supported by a recent study in which videos effectively reduced anxiety scores and improved emotional preparedness of veterinary students prior to anatomy teaching 43 …”
Section: Discussionsupporting
confidence: 77%
“…40,41 Although student anxiety around slaughterhouse visits was reported in our study, the slaughterhouse is not the only learning environment veterinary students encounter that may lead to negative emotions. The surgical environment, 42 the dissection room 43 and EMS 14 can all be a source of anxiety and stress. In line with the results of this study, lack of time to prepare, unclear expectations and lack of self-confidence were all sighted as sources of negative emotions in these other environments.…”
Section: Student Views On Slaughterhouse Visits As Part Of Their Vete...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the preparation of the sessions, the use of videos is very important. Video as a support material for anatomy lectures is considered a very useful resource in a condensed curriculum scenario [36,37], and we have shown that their use can help decrease anxiety and enhance students' learning experience [38]. In our study, students considered these videos as important elements in the preparation of the practicals, although, in some cases, students requested more detailed documents.…”
Section: The Implementation and Usefulness Of Flipped Classroommentioning
confidence: 73%
“…The use of cadavers has primarily been in anatomy and surgical education. Both medical and veterinary students, as well as educators, are emotionally affected by the use of cadavers [2][3][4][5]. In medical education, the use of cadavers and the resulting emotions are driven by a range of ethical issues [3] that are currently much less pronounced in veterinary education [4].…”
Section: Introductionmentioning
confidence: 99%